Co-enrolment to UK Critical Care Studies – A 2019 update. (February 2022) - Felton, Timothy; Pattison, Natalie; Fletcher, Simon; Finney, Simon; Walsh, Tim; Dark, Paul
In 2013, a group of clinicians on behalf of the National Institute for Health Research, collaborated with ICU Steps to produce guidance about people being enrolled in more than one critical care trial. This is referred to as "co-enrolment" and can be where a person takes part in one study at the same time as another study (or one after the other in a short time-frame). For instance, being part of a study looking at sepsis drugs and a mechanical ventilation weaning study. The drivers for developing this guidance were a lack of any existing guidance, nationally and internationally, at that time, and a desire to ensure high quality research is conducted. The emphasis was on making trials as safe as possible for patients and ensuring robust trial outcomes. Critical care was seen to lead in this, with our exemplar guidance used across all health research. We wish to revisit this guidance now that there is more experience of coenrolment in critical care trials. There is also more awareness of different consent models, such as deferred consent (taking consent when a person is awake and able to give consent) and consultee consent (asking families or independent professionals to consent). Consenting to coenrolment is an important ethical consideration for the revision of this guidance.